GAMBARAN PERILAKU SEKS MULTIPARTNER MAHASISWA DALAM PENCEGAHAN KEHAMILAN DAN INFEKSI MENULAR SEKSUAL (IMS) DI KOTA SEMARANG - Eridani Khairunnisa; Zahroh Shaluhiyah; Syamsulhuda Budi Mustofa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Physical, psychological, and social changes in a child will change when experiencing puberty which occurs starting at age 8 to 10 years and ending more or less at the age of 15 to 16 years. During this development period, it is vulnerable for a teenager if there is an imbalance with the growth environment. The Indonesian Family Planning Association (PKBI) in Central Java, 11.2% of dating teenagers held their partner's reproductive organs and 2.4% claimed to have rubbed their reproductive organs into their partners. As a result, there are 50 unwanted pregnancies (KTD) that occur in adolescents aged 13-18 years. The purpose of the study was to determine the behavior of students who have multipartner sex both in the scope of pregnancy prevention and infectious infectious diseases that will occur due to multipartner sex. The approach method used in this study is triangulation by means of Focus Group Discussion (FGD). The research data used is descriptive analysis and uses inductive mindset. Based on the results of the study, it can be concluded that the respondents had a good knowledge of preventing pregnancy and sexual infection. They also make prevention efforts by using safety or condoms when having sexual relations. Health services are still lacking in providing seminars on the prevention of pregnancy and sexual infection and VCT.Keywords : Sex, Multipartner, Pregnancy, Sexual InfectionLiterature : 53 (1997-2019)